Development dimension of competition law and policy - Lachmann, W. (UN New YorkUS, 1999)
Suggests that the competition process does not run smoothly or produce optimal results in developing countries, particulary least developed countries, because of several market imperfections or other limits to competition. Intimates that this would make it particularly necessary for developing countries to adopt and apply competition law and policy.